Pengembangan Budaya Lokal Sebagai Model Pembelajaran Pendidikan Agama Islam di Sekolah Umum Kota Samarinda - Akh Bukhari (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2017)
Development of the local culture as Islamic religious learning model approach is very necessary at this time. Because religion is very in touch with cultural values. Islamic culture such as Habsyian, Manaqiban, reciting sholawat to Prophet Muhammad (solawat Diba '), celebrating Prophet's birthday, and Isro mi'roj, tahlilan, reciting barzanji are becoming increasingly committed by the Muslim community in Ssamarinda. Development of the local culture is not only done among society, but it has touched a post-secondary education institutions, high school and others. It is very interesting because morally is very effective of religious instruction taught religious teachers in their schools. The way how they follow through Manaqib Habsyian and recitation would bring a positive trend among the students. With the performance of the all-white dressed adds spirit to Islam among students. Development of local culture as stated above should be preserved and supported among educators and related agencies. Keep in mind the development of Islam and its spread in Indonesia in conjunction with the local culture as a means of delivery. It almost happened in regions throughout Indonesia as an archipelago country.